Determinantes das taxas de juros à vista e futura no Brasil: uma análise do período 2007-2019 - Citro, Sergio Gozzi (2021)
In the last 25 years, Brazil was among the countries with the highest interest rates in the world, with consequences observed in several fields of the Brazilian economy. High interest rates were necessary, especially in the early years of the Real Plan, starting in 1994. From 1997 to 1999, high interest rates were again observed, due to the following financial crises that hit the country, such as the Mexican (1994), Asian (1997), Russian (1998) and Brazilian (1999). In the midst of macroeconomic vulnerabilities, the Brazilian monetary authority implemented the inflation targeting regime with exchange rate fluctuation, which provided a sustained decreasing track for the interest rate. After a period of relative international calm, the outbreak of the 2008 financial crisis led Brazilian monetary authorities to promote a new round of declining domestic interest rates, in response to the recessive effects and the threat of systemic crisis that hung over the national financial system. As of 2012, a new set of interventionist policies led to a reduction in the Selic rate at a time of inflationary acceleration. In view of the negative effects on the expectations of economic agents, it was necessary to tighten monetary policy and interrupt the downward trend in interest rates. In light of that, it appears that many factors were determinant for the Brazilian interest rates over the years. This work has as main objective to explain, in an empirical way, the determinants of the spot and future interest rate, from the application of a multivariate econometric model of autoregressive vectors (VAR) with error correction (VEC). The relationship between the spot and the future rate is due to the intuitive observation that the future market anticipates the realization of the current market expectations. The period covers from 2007 to 2019, the aftermath of the great global financial crisis of 2008. The results show that both the spot rate and the DI-future can be determined by fluctuations in inflation, the level of economic activity, the real rate exchange rates, in addition to the lagged variables themselves.